1997
DOI: 10.1111/j.1525-1594.1997.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a Synthetic Cornea: Design, Development and Biological Response

Abstract: Our goal was to evaluate 3 different designs of synthetic corneas in vivo. All devices had a transparent hydrogel center molded to a porous peripheral skirt. Over 30 devices were implanted into rabbits and followed for up to 6 months. The devices were preseeded with rabbit stroma1 fibroblasts, which enhanced the rate of fibroplasia. The anterior surface of the hydrogel was modified using argon rf plasma treatments. Clinical examinations were performed, and histological analyses were conducted on tissue through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…Apart from use of AM, it is well known that most applications of biomaterials delay corneal epithelialization (Trinkaus‐Randall et al. ; Hicks et al. ; Ma et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from use of AM, it is well known that most applications of biomaterials delay corneal epithelialization (Trinkaus‐Randall et al. ; Hicks et al. ; Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AM is not transparent, a key shortcoming for visual acuity. Apart from use of AM, it is well known that most applications of biomaterials delay corneal epithelialization (Trinkaus-Randall et al 1997;Hicks et al 2003;Ma et al 2005;Miyashita et al 2006). The ability of a prospective graft material to facilitate a similar rate of epithelialization as the native cornea would indicate that such a material holds promise as an option for corneal grafting.…”
Section: Introductionmentioning
confidence: 99%
“…6 Keratoprostheses should be implanted in a similar way to penetrating keratoplasty. 1,7 Different research groups have synthesized materials to develop an artificial keratoprosthesis (Legais and co-workers, [8][9][10][11][12][13] Chirila and co-workers, [14][15][16][17][18] Trinkaus-Randall and coworkers, [19][20][21][22][23] and von Fischern et al 24 ). Clinical trials using Chirila keratoprosthesis (polyhydroxyethyl methacrylate hydrogel) showed that thick synthetic biocompatible structures can be maintained in the cornea without risk of extrusion, helped by fibroblast ingrowth onto the peripheral portion.…”
Section: Introductionmentioning
confidence: 99%
“…Analizando el proceso completo (comentado en apartado 3. Otro problema importante que se presenta en las membranas fabricadas del modelo core-skirt, es la biointegración de esta con los tejidos circundantes, como ocurre en la Seoul-Type KPro 195,196 , en el modelo propuesto por Trinkaus-Randall et al 192 En caso de implantación de la prótesis, se podría intentar combinar este modelo con sistemas de liberación controlada para mejorar la biointegración, tal y como probó el grupo de Trinkaus et al 193 , o bien implantar la prótesis con un recubrimiento previo de proteínas involucradas en la adhesión 58,192 y/o sembrada con células.…”
Section: Discussionunclassified
“…Entre dichos inconvenientes se destacan, la deposición de partículas en fumadores y formación de depósitos de calcio, tras someter al paciente a determinados tratamientos con fármacos [205][206][207] 192,194 .…”
Section: El Primer Modelo De Córnea Artificial Fue Propuesto Por Guiunclassified